Key indicators for Asia and the Pacific 2021. - Asian Development Bank (Manila,Philippines Asian Development Bank, 2021)
The report covers the 49 regional members of ADB. It discusses trends in development progress and the challenges to achieving inclusive and sustainable economic growth across Asia and the Pacific. This 52nd edition discusses how the COVID-19 pandemic has intensified the challenges of meeting development targets, which needed urgent attention even before the global health crisis began..
Keywords: Sustainable development -- Economic aspects .; Electronic book